1046. Clinical and Microbiological Characteristics of Patients With Septicemia Caused by IMP-1-Producing Enterobacteriaceae in a Tertiary Hospital in Japan. (26th November 2018) - Mori, Nobuaki; Kagawa, Narito; Aoki, Kotaro; Ishii, Yoshikazu; Tateda, Kazuhiro; Aoki, Yasuko
Abstract: Background: Carbapenemase-producing Enterobacteriaceae (CPE) infection has become a great threat to public health worldwide. Although KPC and OXA-48 infections have mostly described, IMP-1 producing Enterobacteriaceae (IMP1-E) are not well studied. We investigated the clinical and microbiological characteristics of septicemia due to the IMP1-E. Methods: This observational study of inpatients who developed IMP-1E septicemia was conducted in a Japanese tertiary hospital from April 2013 to March 2017. IMP1-E was defined as a decreased susceptibility to meropenem (minimum inhibitory concentration, ≥2 mg/L), as well as a positive sodium mercaptoacetic acid test, and polymerase chain reaction for bla IMP genes. Clinical data were collected from medical charts. Antimicrobial susceptibilitly was determined by the MicroScan Walkway. We performed total genomic analysis, plasmid analysis, and multilocus sequence typing (MLST) using whole genome sequencing data. Results: In total, six patients were identified (median age: 55 years). All had severe underlying disease on admission, and five were admitted to the intensive care unit. The sources of IMP1-E septicemia were as follows: two catheter-related BSI, one pyelonephritis, one cholangitis, one bacterial peritonitis, and one unknown focus. Four isolates were Enterobacter cloacae and two were Klebsiella pneumoniae . All patients had a previous history of antibiotic treatment and long-term hospitalization. All patients were treated with either levofloxacin (LVFX) only or LVFX and aminoglycoside (AG). Follow-up blood culture was negative for all patients. All-cause 30-day mortality rate was 50%. Although no isolates were resistant to LVFX and AG, they harbored aac(6')-Ⅱc, sul1, and tet(B ) genes.Two isolates harbored the qnrB6 gene. There was a high probability that bla IMP-1 was carried by IncHI2 plasmids. MLST sequence type of E. cloacae isolates comprised three ST78, and one ST997; K. pneumonia isolates comprised ST134, and ST252. Conclusion: This study showed that IMP1-E septicemia was isolated in patients with severe disease and long-term hospitalization. Selection of antibiotics therapy based on antimicrobial susceptibility induced microbiological cure, but clinical response was dependent on the underlying diseases. Disclosures: All authors: No reported disclosures.